2006
DOI: 10.1053/j.gastro.2006.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Hint2, A Mitochondrial Apoptotic Sensitizer Down-Regulated in Hepatocellular Carcinoma

Abstract: Background & Aims: Hints, Histidine triad nucleotide-binding proteins, are adenosine monophosphate-lysine hydrolases of uncertain biological function. Here we report the characterization of human Hint2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
3
53
0
2
Order By: Relevance
“…We have shown low expression of HINT2 in endometrial cancer cells compared with control cells and expression of HINT2 was upregulated by progesterone and calcitriol treatment. These results are in agreement with a study suggesting that HINT2 overexpression sensitizes hepatocellular carcinoma to apoptosis (57).…”
Section: Discussionsupporting
confidence: 93%
“…We have shown low expression of HINT2 in endometrial cancer cells compared with control cells and expression of HINT2 was upregulated by progesterone and calcitriol treatment. These results are in agreement with a study suggesting that HINT2 overexpression sensitizes hepatocellular carcinoma to apoptosis (57).…”
Section: Discussionsupporting
confidence: 93%
“…BCATm KO was also Tables S1-S3). Hint1 appears to regulate proteasomal degradation of proteins by the SKP2-CUL1-F-box protein-E3 ubiquitin-protein ligase complex, whereas the mitochondrial isoform, Hint2, has been described as an apoptotic sensitizer (16,57). Increased expression of two genes that are linked to positive regulation of apoptosis, cytochrome C somatic (Cycs) and BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (Bbip3, the most highly expressed member of this family in muscle), were also increased (Supplementary Tables S1-S2, notably no caspase genes were affected though).…”
Section: Resultsmentioning
confidence: 99%
“…Our overexpression experiments indicated that HINT2 but not HINT3 was also able to catalyze the deamination reaction. However, it is likely that HINT1 is the major enzyme for GS-6620 activation, since HINT2 is a mitochondrial enzyme (21,22). The monophosphate metabolite must be phosphorylated to the active triphosphate form, GS-441326, by cellular nucleotide kinases.…”
Section: Discussionmentioning
confidence: 99%